Nitrogen-doped lithium iron phosphate as well as preparation method and application thereof
By using starch and nitrogen -containing composite carbon source nitrogen -prepared nitrogen doped iron phosphate, it solves the problem of uneven carbon coverage of lithium iron phosphate orthopedic material, which is difficult to regulate and difficult to regulate the particle size, and significantly improves its multiplier performance.
Patent Information
- Application Number
- CN202411272319.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-01-28
AI Technical Summary
In the prior art, the carbon coating of lithium iron phosphate positive electrode material is uneven and the particle size is difficult to regulate, resulting in less obvious improvement effect of rate performance.
Use starch and compound carbon sources with nitrogen -containing compounds to prepare the predecessor driving pulp before the lithium iron phosphate. It is burned by spraying dry and inert atmosphere to prepare lithium iron phosphate mixed with nitrogen doped.
The uniform carbon coverage of lithium iron phosphate is realized, and its magnification performance is improved, especially the capacity of the discharge ratio at a large rate is significantly improved.
Smart Images

Figure CN119370815A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to nitrogen-doped lithium iron phosphate and a preparation method and application thereof. Background Art
[0002] Lithium ion battery (LIB) is currently the most promising and fastest-growing high-efficiency secondary battery, with many advantages such as environmental friendliness, high specific energy, good thermal stability, good cycle performance, and no memory effect.
[0003] Lithium iron phosphate / carbon cathode materials have good electrochemical and safety properties, and meet the needs of lithium-ion power batteries to develop in the direction of high energy density and low cost. Although lithium iron phosphate has many advantages as a cathode material for lithium-ion batteries, it also has problems such as poor conductivity and low lithium ion diffusion coefficient. The existing technical methods usually use traditional carbon materials such as glucose, sucrose, and polyethylene glycol to coat and modify lithium iron phosphate. Although the electronic conductivity of lithium iron phosphate cathode materials has been improved to a certain extent, the above method has problems such as uneven carbon coating and difficult to control particle size, so the improvement effect of its rate performance is not very obvious.
[0004] CN 115611256A discloses a method for preparing lithium iron phosphate, comprising the following steps: (1) mixing a lithium source, an iron source, and a phosphorus source uniformly, and then adding a mixed carbon source (sucrose mixed with polyethylene glycol; or glucose mixed with polyethylene glycol; or sucrose mixed with glucose) and water to mix uniformly; (2) grinding and drying the mixture to obtain a precursor; (3) sintering the precursor under an inert atmosphere, and then crushing, screening, and demagnetizing to obtain the lithium iron phosphate. Although this method improves the problem of uneven carbon coating on the surface of lithium iron phosphate, it does not completely achieve uniform carbon coating on lithium iron phosphate, and the improvement in rate performance is not very obvious, and the 1C discharge specific capacity is only 145mAh / / g. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a nitrogen-doped lithium iron phosphate and a preparation method and application thereof.
[0006] The technical solution of the present invention is as follows:
[0007] The present invention provides a method for preparing nitrogen-doped lithium iron phosphate, comprising the following steps:
[0008] S1. Ball-milling and mixing iron phosphate, lithium carbonate, starch and nitrogen-containing compounds in water to form lithium iron phosphate precursor slurry;
[0009] S2, spray drying the precursor slurry obtained in step S1 to obtain lithium iron phosphate precursor powder;
[0010] S3, calcining the lithium iron phosphate precursor powder obtained in step S2 under an inert atmosphere to obtain nitrogen-doped lithium iron phosphate powder.
[0011] In S1, ball milling is used to mix the raw materials so that D50 is less than 0.5 um and the raw materials are fully mixed.
[0012] Furthermore, the carbon source of the nitrogen-containing compound in S1 is at least one of melamine, polyaniline, polyvinyl pyrrolidone, polypyrrole, and urea.
[0013] Furthermore, the molar ratio of the lithium carbonate in S1 to the lithium iron in the iron phosphate is 1.0 to 1.1:1.
[0014] Furthermore, the ball milling time in S1 is 80 min to 270 min.
[0015] Furthermore, the carbon content of the nitrogen-doped lithium iron phosphate powder described in S3 is 1.0% to 2.0% by mass.
[0016] Furthermore, the inlet air temperature of the spray drying in S2 is 150-250°C.
[0017] Furthermore, the inert atmosphere in S3 is at least one of nitrogen and argon.
[0018] Furthermore, the calcination temperature in S3 is 650-800° C., and the calcination time is 6-15 hours.
[0019] Furthermore, the nitrogen content of the nitrogen-doped lithium iron phosphate powder described in S3 is ≤1000 ppm.
[0020] The present invention also provides nitrogen-doped lithium iron phosphate, which is prepared by the above-mentioned preparation method.
[0021] The present invention also provides a method for preparing a nitrogen-doped lithium iron phosphate positive electrode material, comprising the following steps:
[0022] The nitrogen-doped lithium iron phosphate, conductive carbon and polyvinylidene fluoride are mixed in a mass ratio of 90%:5%:5%, adjusted with N-methylpyrrolidone, stirred into a viscous state, applied on aluminum foil, dried at 120°C in vacuum for 3 hours, and cut into circular films with a diameter of about 1 cm after cooling.
[0023] The present invention also provides a nitrogen-doped lithium iron phosphate positive electrode material, which is prepared by the above-mentioned preparation method.
[0024] The present invention also provides an application of a nitrogen-doped lithium iron phosphate positive electrode material in a lithium ion battery.
[0025] Due to the adoption of the above technical solution, the beneficial effects of the present invention are as follows:
[0026] 1. The method of the present invention can solve the problems of uneven carbon coating and difficult to control particle size in the current use of common carbon sources such as sucrose, glucose, and polyethylene glycol to coat lithium iron phosphate positive electrode materials; improve the rate performance of lithium iron phosphate, especially the high rate performance. The discharge specific capacity at 1C rate is above 161mAh / g; at 10C rate, the discharge specific capacity is above 141mAh / g.
[0027] 2. The present invention adds a composite carbon source mixture of starch and nitrogen-containing compounds to prepare lithium iron phosphate precursor slurry. The composite carbon source can make the carbon coating of lithium iron phosphate more uniform. In addition, the nitrogen-containing compound can also be used as a non-metallic nitrogen-doped substance. The presence of nitrogen can make the carbon of lithium iron phosphate uniformly coated, which is confirmed in the energy spectrum diagram below.
[0028] 3. The technical solution of the present invention uses water as the solvent. Compared with anhydrous ethanol as the solvent, there is no significant difference in dispersion, but the production cost is greatly reduced, and the production process is simple and easy to operate. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is the microscopic morphology of lithium iron phosphate in the manual;
[0030] Figure 2 This is the EDS image of the lithium iron phosphate micromorphology in the manual;
[0031] Figure 3 is the XRD diffraction pattern of nitrogen-doped lithium iron phosphate in Example 1;
[0032] Figure 4 This is a graph of the rate discharge performance of button batteries comparing the nitrogen-doped lithium iron phosphate in Example 1 with the traditional lithium iron phosphate in Comparative Example 1. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0034] Example 1
[0035] This embodiment provides a method for preparing nitrogen-doped lithium iron phosphate, comprising the following steps:
[0036] Iron phosphate and lithium carbonate are dispersed in pure water at a lithium-iron molar ratio of 1:1, 10wt% (accounting for the theoretical mass of lithium iron phosphate) of starch is added, and then 10% (accounting for the theoretical mass of synthetic lithium iron phosphate) of melamine is added, and after ball milling for 4 hours, spray drying is performed, and the inlet air temperature of the spray drying is 200°C; the precursor obtained by spray drying is heated from room temperature to 750°C under a nitrogen atmosphere and maintained at 750°C for 12 hours, and taken out after cooling to obtain nitrogen-doped lithium iron phosphate powder; the carbon content mass ratio in the nitrogen-doped lithium iron phosphate powder is 1.35%, and the nitrogen content of the nitrogen-doped lithium iron phosphate powder is 400ppm.
[0037] The obtained nitrogen-doped lithium iron phosphate powder was subjected to XRD diffraction, and the obtained XRD diffraction pattern is shown in Figure 3 As shown; comparing the XRD diffraction pattern with the standard card of lithium iron phosphate, it is proved that lithium iron phosphate is prepared and no impurities are generated after doping with nitrogen.
[0038] Example 2
[0039] This embodiment provides a method for preparing nitrogen-doped lithium iron phosphate, comprising the following steps:
[0040] Iron phosphate and lithium carbonate are dispersed in pure water at a lithium-iron molar ratio of 1:1, 10wt% (accounting for the theoretical mass of lithium iron phosphate) of starch is added, and then 10% (accounting for the theoretical mass of synthetic lithium iron phosphate) of polyaniline is added, and after ball milling for 4 hours, spray drying is performed, and the inlet air temperature of the spray drying is 200°C; the precursor obtained by spray drying is heated from room temperature to 750°C in a nitrogen atmosphere and maintained at 750°C for 12 hours, and taken out after cooling to obtain nitrogen-doped lithium iron phosphate powder; the carbon content mass ratio in the nitrogen-doped lithium iron phosphate powder is 1.40%, and the nitrogen content of the nitrogen-doped lithium iron phosphate powder is 150ppm.
[0041] Example 3
[0042] This embodiment provides a method for preparing nitrogen-doped lithium iron phosphate, comprising the following steps:
[0043] Iron phosphate and lithium carbonate are dispersed in pure water at a lithium-iron molar ratio of 1:1, 10wt% (accounting for the theoretical mass of lithium iron phosphate) of starch is added, and then 5% (accounting for the theoretical mass of synthesized lithium iron phosphate) of melamine and 5% (accounting for the theoretical mass of synthesized lithium iron phosphate) of polyaniline are added, and after ball milling for 4 hours, spray drying is performed, and the inlet air temperature of the spray drying is 200°C; the precursor obtained by spray drying is heated from room temperature to 750°C in a nitrogen atmosphere and maintained at 750°C for 12 hours, and taken out after cooling to obtain nitrogen-doped lithium iron phosphate powder; the carbon content mass ratio in the nitrogen-doped lithium iron phosphate powder is 1.37%, and the nitrogen content of the nitrogen-doped lithium iron phosphate powder is 300ppm.
[0044] Example 4
[0045] This embodiment provides a method for preparing nitrogen-doped lithium iron phosphate, comprising the following steps:
[0046] Iron phosphate and lithium carbonate are dispersed in pure water at a lithium-iron molar ratio of 1:1, 10wt% (accounting for the theoretical mass of lithium iron phosphate) of starch is added, and then 10% (accounting for the theoretical mass of synthetic lithium iron phosphate) of polyvinyl pyrrolidone is added. After ball milling for 4 hours, spray drying is performed, and the inlet air temperature of the spray drying is 200°C; the precursor obtained by spray drying is heated from room temperature to 750°C under a nitrogen atmosphere and maintained at 750°C for 12 hours, and taken out after cooling to obtain nitrogen-doped lithium iron phosphate powder; the carbon content mass ratio in the nitrogen-doped lithium iron phosphate powder is 1.30%, and the nitrogen content of the nitrogen-doped lithium iron phosphate powder is 145ppm.
[0047] Example 5
[0048] This embodiment provides a method for preparing nitrogen-doped lithium iron phosphate, comprising the following steps:
[0049] Iron phosphate and lithium carbonate are dispersed in pure water at a lithium-iron molar ratio of 1:1, 10wt% (accounting for the theoretical mass of lithium iron phosphate) of starch is added, and then 10% (accounting for the theoretical mass of synthetic lithium iron phosphate) of polypyrrole is added, and after ball milling for 4 hours, spray drying is performed, and the inlet air temperature of the spray drying is 200°C; the precursor obtained by spray drying is heated from room temperature to 750°C in a nitrogen atmosphere and maintained at 750°C for 12 hours, and taken out after cooling to obtain nitrogen-doped lithium iron phosphate powder; the carbon content mass ratio in the nitrogen-doped lithium iron phosphate powder is 1.38%, and the nitrogen content of the nitrogen-doped lithium iron phosphate powder is 200ppm.
[0050] Example 6
[0051] This embodiment provides a method for preparing nitrogen-doped lithium iron phosphate, comprising the following steps:
[0052] Iron phosphate and lithium carbonate are dispersed in pure water at a lithium-iron molar ratio of 1:1, 10wt% (accounting for the theoretical mass of lithium iron phosphate) of starch is added, and then 10% (accounting for the theoretical mass of synthetic lithium iron phosphate) of urea is added. After ball milling for 4 hours, spray drying is performed, and the inlet air temperature of the spray drying is 200°C; the precursor obtained by spray drying is heated from room temperature to 750°C under a nitrogen atmosphere and maintained at 750°C for 12 hours, and taken out after cooling to obtain nitrogen-doped lithium iron phosphate powder; the carbon content mass ratio in the nitrogen-doped lithium iron phosphate powder is 1.2%, and the nitrogen content of the nitrogen-doped lithium iron phosphate powder is 350ppm.
[0053] Example 7
[0054] This embodiment provides a method for preparing nitrogen-doped lithium iron phosphate, comprising the following steps:
[0055] Iron phosphate and lithium carbonate are dispersed in pure water at a lithium-iron molar ratio of 1:1, 10wt% (accounting for the theoretical mass of lithium iron phosphate) of starch is added, and then 5% (accounting for the theoretical mass of synthesized lithium iron phosphate) of polyvinyl pyrrolidone and 5% (accounting for the theoretical mass of synthesized lithium iron phosphate) of melamine are added, and after ball milling for 4 hours, spray drying is performed, and the inlet air temperature of the spray drying is 200°C; the precursor obtained by spray drying is heated from room temperature to 750°C in a nitrogen atmosphere and maintained at 750°C for 12 hours, and taken out after cooling to obtain nitrogen-doped lithium iron phosphate powder; the carbon content mass ratio in the nitrogen-doped lithium iron phosphate powder is 1.32%, and the nitrogen content of the nitrogen-doped lithium iron phosphate powder is 230ppm.
[0056] Example 8
[0057] This embodiment provides a method for preparing nitrogen-doped lithium iron phosphate, comprising the following steps:
[0058] Iron phosphate and lithium carbonate are dispersed in pure water at a lithium-iron molar ratio of 1:1, 10wt% (accounting for the theoretical mass of lithium iron phosphate) of starch is added, and then 5% (accounting for the theoretical mass of synthesized lithium iron phosphate) of polypyrrole and 5% (accounting for the theoretical mass of synthesized lithium iron phosphate) of melamine are added, and after ball milling for 4 hours, spray drying is performed, and the inlet air temperature of the spray drying is 200°C; the precursor obtained by spray drying is heated from room temperature to 750°C under a nitrogen atmosphere and maintained at 750°C for 12 hours, and taken out after cooling to obtain nitrogen-doped lithium iron phosphate powder; the carbon content mass ratio in the nitrogen-doped lithium iron phosphate powder is 1.36%, and the nitrogen content of the nitrogen-doped lithium iron phosphate powder is 350ppm.
[0059] Example 9
[0060] The preparation method of nitrogen-doped lithium iron phosphate positive electrode material adopts the following steps:
[0061] The sample to be tested, conductive carbon and polyvinylidene fluoride are mixed in a mass ratio of 90%:5%:5%, adjusted with N-methylpyrrolidone, stirred into a viscous state, applied on aluminum foil, dried at 120°C in vacuum for 3 hours, and cut into circular films with a diameter of about 1 cm after cooling.
[0062] Example 10
[0063] The application of nitrogen-doped lithium iron phosphate cathode material in lithium-ion batteries is as follows:
[0064] The nitrogen-doped lithium iron phosphate positive electrode material was assembled in a glove box using a CR2016 button cell. The diaphragm was a Celgard2325 polypropylene diaphragm, the electrolyte was a 1M LiPF6 mixed electrolyte of ethylene carbonate (EC) and diethyl carbonate (DEC) (the volume ratio of EC and DEC in the mixed electrolyte was 1:1, and the LiPF6 concentration in the mixed electrolyte was 1M), and the negative electrode was a commercial round lithium sheet.
[0065] Comparative Example 1
[0066] This comparative example provides a method for preparing a conventional lithium iron phosphate, comprising the following steps:
[0067] Iron phosphate and lithium carbonate are dispersed in pure water in a lithium-iron molar ratio of 1:1, and then 10% (accounting for the theoretical mass of synthesized lithium iron phosphate) of glucose is added. After ball milling for 4 hours, spray drying is performed, and the inlet air temperature of the spray drying is 200°C; the precursor obtained by spray drying is heated from room temperature to 750°C under a nitrogen atmosphere and maintained at 750°C for 12 hours, and then taken out after cooling to obtain traditional lithium iron phosphate powder; the carbon content mass ratio of the lithium iron phosphate powder is 1.30%.
[0068] Comparative Example 2
[0069] Iron phosphate and lithium carbonate are dispersed in pure water in a lithium-iron molar ratio of 1:1, and then 10% (accounting for the theoretical mass of synthesized lithium iron phosphate) of sucrose is added. After ball milling for 4 hours, spray drying is performed, and the inlet air temperature of the spray drying is 200°C; the precursor obtained by spray drying is heated from room temperature to 750°C under a nitrogen atmosphere and maintained at 750°C for 12 hours, and taken out after cooling to obtain traditional lithium iron phosphate powder; the carbon content mass ratio of the lithium iron phosphate powder is 1.35%.
[0070] Comparative Example 3
[0071] This comparative example provides a method for preparing nitrogen-doped lithium iron phosphate when the molar ratio of lithium iron is too large, comprising the following steps:
[0072] Disperse iron phosphate and lithium carbonate in pure water at a molar ratio of lithium to iron of 1.15:1, add 10wt% (accounting for the theoretical mass of lithium iron phosphate) starch, and then add 10% (accounting for the theoretical mass of synthetic lithium iron phosphate) melamine, ball mill for 4 hours, spray dry, and the inlet air temperature of spray drying is 200°C; the precursor obtained by spray drying is heated from room temperature to 750°C in a nitrogen atmosphere and maintained at 750°C for 12 hours, and then taken out after cooling to obtain nitrogen-doped lithium iron phosphate powder. The carbon content mass ratio of the nitrogen-doped lithium iron phosphate powder is 1.30%, and the nitrogen content of the nitrogen-doped lithium iron phosphate powder is 400ppm.
[0073] Comparative Example 4
[0074] This comparative example provides a method for preparing nitrogen-doped lithium iron phosphate with an excessively high carbon content, comprising the following steps:
[0075] Iron phosphate and lithium carbonate are dispersed in pure water at a molar ratio of 1:1 between lithium and iron, 30wt% (accounting for the theoretical mass of lithium iron phosphate) starch is added, and then 10% (accounting for the theoretical mass of synthetic lithium iron phosphate) polyaniline is added, ball milled for 4 hours, spray dried, and the inlet air temperature of spray drying is 200°C; the precursor obtained by spray drying is heated from room temperature to 750°C in a nitrogen atmosphere and maintained at 750°C for 12 hours, and taken out after cooling to obtain nitrogen-doped lithium iron phosphate powder. The carbon content mass ratio of the nitrogen-doped lithium iron phosphate powder is 2.30%, and the nitrogen content of the nitrogen-doped lithium iron phosphate powder is 150ppm.
[0076] Comparative Example 5
[0077] This comparative example provides a method for preparing nitrogen-doped lithium iron phosphate with an excessively high nitrogen content, comprising the following steps:
[0078] Iron phosphate and lithium carbonate are dispersed in pure water at a lithium-iron molar ratio of 1:1, 10wt% (accounting for the theoretical mass of lithium iron phosphate) of starch is added, and then 60% (accounting for the theoretical mass of synthetic lithium iron phosphate) of melamine is added, and after ball milling for 4 hours, spray drying is performed, and the inlet air temperature of the spray drying is 200°C; the precursor obtained by spray drying is heated from room temperature to 750°C under a nitrogen atmosphere and maintained at 750°C for 12 hours, and taken out after cooling to obtain nitrogen-doped lithium iron phosphate powder; the carbon content mass ratio in the nitrogen-doped lithium iron phosphate powder is 1.50%, and the nitrogen content of the nitrogen-doped lithium iron phosphate powder is 2400ppm.
[0079] Comparative Example 6
[0080] This comparative example provides a method for preparing nitrogen-doped lithium iron phosphate with a low nitrogen content, comprising the following steps:
[0081] Iron phosphate and lithium carbonate are dispersed in pure water at a lithium-iron molar ratio of 1:1, 10wt% (accounting for the theoretical mass of lithium iron phosphate) of starch is added, and then 1% (accounting for the theoretical mass of synthetic lithium iron phosphate) of melamine is added, and after ball milling for 4 hours, spray drying is performed, and the inlet air temperature of the spray drying is 200°C; the precursor obtained by spray drying is heated from room temperature to 750°C under a nitrogen atmosphere and maintained at 750°C for 12 hours, and taken out after cooling to obtain nitrogen-doped lithium iron phosphate powder; the carbon content mass ratio in the nitrogen-doped lithium iron phosphate powder is 1.25%, and the nitrogen content of the nitrogen-doped lithium iron phosphate powder is 40ppm.
[0082] The electrochemical performance of the lithium iron phosphate positive electrode materials prepared in Examples 1-8 and Comparative Examples 1-6 was measured, and the electrochemical performance test was carried out on a BlueDian 5V5MA8CT battery test system (produced by Wuhan BlueDian Electronics Co., Ltd.).
[0083] After the rate test, the discharge capacities of the samples of Examples 1-8 and Comparative Examples 1-6 are shown in the following table:
[0084] Table 1. Discharge specific capacity of samples of Examples 1-8 and Comparative Examples 1-6 at 1C and 10C after rate test
[0085]
[0086] It can be seen from the above table:
[0087] In addition, the discharge performance comparison between Example 1 and Comparative Example 1 is shown in the attached figure. Figure 4 It can be seen that the discharge performance of nitrogen-doped lithium iron phosphate is significantly better than that of traditional lithium iron phosphate.
[0088] Comparative Example 3 shows that when the lithium iron phosphate precursor slurry is prepared, if the lithium iron molar ratio is too large, the discharge specific capacity of the lithium iron phosphate will be reduced.
[0089] Comparative Example 4 shows that when the carbon content of nitrogen-doped lithium iron phosphate powder is too high, the discharge specific capacity of lithium iron phosphate will also be reduced.
[0090] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing nitrogen-doped lithium iron phosphate, characterized in that: The steps include: S1. Ball-milling and mixing iron phosphate, lithium carbonate, starch and nitrogen-containing compounds in water to form lithium iron phosphate precursor slurry; S2, spray drying the precursor slurry obtained in step S1 to obtain lithium iron phosphate precursor powder; S3, calcining the lithium iron phosphate precursor powder obtained in step S2 under an inert atmosphere to obtain nitrogen-doped lithium iron phosphate powder.
2. The method for preparing nitrogen-doped lithium iron phosphate according to claim 1, characterized in that: The carbon source of the nitrogen-containing compound in S1 is at least one of melamine, polyaniline, polyvinyl pyrrolidone, polypyrrole and urea.
3. The method for preparing nitrogen-doped lithium iron phosphate according to claim 1, characterized in that: The molar ratio of the lithium carbonate in S1 to the lithium iron in the iron phosphate is 1.0 to 1.1:
1.
4. The method for preparing nitrogen-doped lithium iron phosphate according to claim 1, characterized in that: The carbon content of the nitrogen-doped lithium iron phosphate powder described in S3 is 1.0% to 2.0% by mass.
5. The method for preparing nitrogen-doped lithium iron phosphate according to claim 1, characterized in that: The inlet air temperature of the spray drying in S2 is 150-250°C.
6. The method for preparing nitrogen-doped lithium iron phosphate according to claim 1, characterized in that: The calcination temperature in S3 is 650-800° C., and the calcination time is 6-15 hours; the inert atmosphere is at least one of nitrogen and argon.
7. A nitrogen-doped lithium iron phosphate, characterized in that: Prepared by the preparation method according to any one of claims 1 to 6.
8. A nitrogen-doped lithium iron phosphate positive electrode material, characterized in that: It is prepared by using the nitrogen-doped lithium iron phosphate as claimed in claim 7.
9. Application of nitrogen-doped lithium iron phosphate positive electrode material in lithium-ion batteries, characterized in that: Application of the nitrogen-doped lithium iron phosphate positive electrode material according to claim 8 in lithium-ion batteries.
Citation Information
Cited By
Preparation method of nitrogen-doped modified lithium iron phosphate positive electrode material
CN121269665A